Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Optoelectronic photoinduced charge transfer system with mu 3PhN-Ru-3 cluster functionalized single-walled carbon nanotubes - Lee, Wonjoo; Koo, Gumae; Ogale, Satishchandra B.; Han, Sung-Hwan (Journal of Materials Chemistry C, 2009)
Optoelectronic photoinduced charges have been attracting great attention lately in view of their applicability to diverse optoelectronic device systems. Here, we report the design and implementation of a charge transfer system based on triruthenium (Ru) cluster compounds on viologen modified single-walled carbon nanotubes (V-SWNTs) by an in situ preparation method. We examine the photoinduced (intensity dependent and temporal) changes in the transport properties of the Ru-cluster functionalized V-SWNT coating and identify the possible charge transfer mechanism. Furthermore, we demonstrate the applicability of such Ru-cluster functionalized V-SWNT films to photoelectrochemical cells.

Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2